2016
DOI: 10.1590/1809-4430-eng.agric.v36n1p94-101/2016
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation time of the spring sorghum as a predecessor crop for summer soybean and autumn bean in a no-tillage system

Abstract: Several authors have been questioned the desiccation interval between the coverage plants and sowing plants for the soybean crop. Therefore, this study aimed to evaluate the desiccation time of the spring sorghum as a predecessor crop for summer soybean and then for autumn bean, focusing on the straw formation for maintenance of the no-tillage system and to evaluate the yield of soybeans and beans grain, as well as analyzing the interference of sorghum straw in these cultures. The experiment was developed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Cover species such as sorghum (Sorghum bicolor L.) cause soybean suppression by releasing allelopathic compounds with yield effects (Denadai, De Mello, Chioderoli, & De Niro Gazola, 2016), however, for Almeida (1991), allelopathic compounds released by cereal rye, oilseed radish and oat (Avena sativa) roots do not interfere in the germination percentage of soybean seeds. Bortolini and Fortes (2005), studying allelopathy caused by cover crops, concluded that root exudates from black oat and hairy vetch plants do not reduce soybean seed germination.…”
Section: Soybean Yieldmentioning
confidence: 99%
“…Cover species such as sorghum (Sorghum bicolor L.) cause soybean suppression by releasing allelopathic compounds with yield effects (Denadai, De Mello, Chioderoli, & De Niro Gazola, 2016), however, for Almeida (1991), allelopathic compounds released by cereal rye, oilseed radish and oat (Avena sativa) roots do not interfere in the germination percentage of soybean seeds. Bortolini and Fortes (2005), studying allelopathy caused by cover crops, concluded that root exudates from black oat and hairy vetch plants do not reduce soybean seed germination.…”
Section: Soybean Yieldmentioning
confidence: 99%
“…Olibone et al (2006) verificaram efeito alopático de exsudatos de sorgo na redução da taxa de germinação e desenvolvimento de plântulas de soja cultivadas em vasos. Em condições de campo, Denadai et al (2016) verificaram efeito nocivo de 9 ton ha -1 de matéria seca de sorgo incorporada ao solo sobre o cultivo de soja em sucessão, quando feita a dessecação química com glyphosate na dose de 1,44 kg i.a.…”
unclassified